Long-Term Increase in Cholesterol Is Associated With Better Cognitive Function: Evidence From a Longitudinal Study - Liu, Huamin; Zou, Lianwu; Zhou, Rui; Zhang, Minyi; Gu, Shanyuan; Zheng, Jiazhen; Hukportie, Daniel Nyarko; Wu, Keyi; Huang, Zhiwei; Yuan, Zelin; Wu, Xianbo (Frontiers in Aging Neuroscience, 2021)
Background: Higher visit-to-visit cholesterol has been associated with cognitive decline. However, the association between long-term increase or decrease in cholesterol and cognitive decline remains unclear. Methods: A total of 4,915 participants aged ≥ 45 years with normal cognition in baseline were included. The participants were divided into four groups, namely, low–low, low–high, high–low and high–high, according to the diagnostic thresholds of total cholesterol (TC), non-high-density lipoprotein cholesterol (NHDL-C), low-density lipoprotein cholesterol and high-density lipoprotein cholesterol (HDL-C) after four years of follow-up. Cognitive function was assessed by episodic memory and mental intactness. Binary logistic regression was used to analyse the association of cholesterol variation with cognitive decline. Results: Amongst the participants, 979 (19.9%) experienced global cognitive decline. The odds ratio (OR) of global cognitive decline and memory function decline were remarkably lower in the participants in the low–high NHDL-C group than those in the low–low group (OR and 95% confidence interval [CI]: 0.50 [0.26-0.95] for global cognitive decline, 0.45 [0.25-0.82] for memory function decline). The lower OR was also significant in females (OR [95% CI]: 0.38 [0.17-0.87] for global cognitive decline; 0.44 [0.19-0.97] for memory function decline) and participants without cardiovascular disease (OR [95% CI]: 0.31 [0.11-0.87] for global cognitive decline; 0.34 [0.14-0.83] for memory function decline). The increases of other cholesterol were also negatively associated with the risk of cognitive decline, although not significant. Conclusions: A longitudinal increase in NHDL-C may be protective for cognition in females or individuals without cardiovascular disease.